Profile of musculoskeletal injuries in the parasport: A systematic review - Santos Silva Lopes, J.; Monteiro de Magalhaes Neto, A.; Flauzino Machado, A.; Castilho de Almeida, A.; Maria Lopes, S.; Marlise Balbinotti Andrade, C. (Science & Sports, 2022)
Background Despite the benefits of sport, it is known that, sports practice increases the exposure to and incidence of sports injuries. Therefore, studies are needed that demonstrate the injury patterns associated with parasports, which will prospectively allow the suggestion of specific preventive protocols. Objective Demonstrate the profile of injuries in parasports, in different sports and types of disability. Data sources Searches were conducted in the PubMed/MEDLINE, EMBASE, PEDro, Cochrane, SportsDiscus, and Scielo databases until March 2020. The search terms included combinations of keywords related to parasports and sports injuries. To be included, studies were required to: (1) target disabled athletes; (2) evaluate amateur or professional levels; and (3) verify measures of sports injuries. Results Thirty one studies (n = 17,608 participants) were included. It was found a higher prevalence of injuries in muscle fibers, and in modalities practiced in a standing position. The anatomical site with the highest incidence was the lower limbs, especially the thigh, while, in sitting position sports, in water and in competitions, the highest incidence was observed in upper limbs, especially the shoulder. Conclusion These findings provide clinicians and researchers with parameters to guide the prescription of specific preventive interventions, considering the type of sport submodality practiced.